(3a+2b)+(-3a+b)=0

Simple and best practice solution for (3a+2b)+(-3a+b)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a+2b)+(-3a+b)=0 equation:


Simplifying
(3a + 2b) + (-3a + b) = 0

Remove parenthesis around (3a + 2b)
3a + 2b + (-3a + b) = 0

Remove parenthesis around (-3a + b)
3a + 2b + -3a + b = 0

Reorder the terms:
3a + -3a + 2b + b = 0

Combine like terms: 3a + -3a = 0
0 + 2b + b = 0
2b + b = 0

Combine like terms: 2b + b = 3b
3b = 0

Solving
3b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Divide each side by '3'.
b = 0

Simplifying
b = 0

See similar equations:

| 10x+2=4x+5 | | 2x+3=-5x+7/2 | | 9x-(2x-8)=0 | | 64=-3x-4(-x-13) | | x+x=170 | | 900=540+90n | | 1.3x=21 | | -4x+8=52+7x | | x-4x+4=4-3x | | 11(7y-2)=0 | | 12-n=23 | | 7(6x+x)+3(1+7x)=-18 | | 8*24w=432 | | 5+3(x-4)=11 | | x-3+5=x | | -(1+7p)+8(-3p+2)=-18 | | -5y=10-3x | | 360=4n | | 7x+5=x+10 | | 7X-22=X+18 | | 3(x+3)=(x+3)+x+(2x-3) | | -(-m+n+1)=0 | | 6x+7=4+2x | | 2(3x-2)-2(4x+3)=4 | | 3+3=6 | | (2+1.5)n=10.5 | | 94y+100=100y-80 | | z+4=8 | | -1-4(7y-1)=2(-6y-8)+3 | | 2(x+9)+2x+2+5x-4=89 | | 7(8+7b)+8(-5b-8)=28 | | 0(-2x)=4 |

Equations solver categories